2002
DOI: 10.1006/icar.2002.6841
|View full text |Cite
|
Sign up to set email alerts
|

Planetary Bioresources and Astroecology 1. Planetary Microcosm Bioassays of Martian and Carbonaceous Chondrite Materials: Nutrients, Electrolyte Solutions, and Algal and Plant Responses

Abstract: The biological fertilities of planetary materials can be assessed using microcosms based on meteorites. This study applies microcosm tests to martian meteorites and analogues and to carbonaceous chondrites. The biological fertilities of these materials are rated based on the soluble electrolyte nutrients, the growth of mesophile and cold-tolerant algae, and plant tissue cultures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…4) [8,9,14]. We also found that brine shrimp eggs can uptake meteorite materials and can hatch in meteorite extracts, which shows that the extracts are not significantly toxic.…”
Section: Biomass Yield From Element (G/kg)mentioning
confidence: 53%
See 3 more Smart Citations
“…4) [8,9,14]. We also found that brine shrimp eggs can uptake meteorite materials and can hatch in meteorite extracts, which shows that the extracts are not significantly toxic.…”
Section: Biomass Yield From Element (G/kg)mentioning
confidence: 53%
“…The biomass that can be constructed from element x in a resource material is given by Equation (3) [8,9].…”
Section: Relations Between Resources and Biomassmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbial interactions with planetary regolith could also be used to control and prevent regolith moving downslope (mass movement) in enclosed settings (Liu et al 2008) or be used as the precursor to soil formation (Mautner 2002;Kral et al 2004;Lytvynenko et al 2006).…”
Section: Introductionmentioning
confidence: 99%